Genetics analysis for earliness and yield traits using Ogura CMS in snowball cauliflower (Brassica oleracea var. botrytis) - RAM, HANUMAN; SUREJA, AMISH K; DEY, S S; TOMAR, B S (The Indian Journal of Agricultural Sciences, 2019)
A study was undertaken to determine the components of genetic variance and gene action effects in snowball cauliflower (Brassica oleracea var. botrytis L.) lines through line × tester analysis involving 5 Ogura CMS lines and 7 male fertile testers. The mean squares due to lines and testers were significant for most of the characters under study, except for gross plant weight, polar diameter, equatorial diameter, curd weight, curd yield and harvest index and for line × tester, it was significant for leaf length, leaf width, number of leaves per plant, plant height, days to 50% curd initiation and days to 50% curd maturity. Pre-dominance of dominance component of variance was observed for leaf length, number of leaves per plant, plant height, days to 50% curd initiation, marketable curd weight and marketable curd yield. The traits studied had narrow differences among GCV, PCV and broad sense heritability values, suggesting low effect of environment on the expression of phenotype for most of vegetative traits. The variance due to general (σ2gca) and specific combining abilities (σ2sca) were highly significant indicating the importance of both additive (σ2A) as well as non-additive (σ2D) type of gene actions. However, the ratios of σ2gca/ σ2sca (<1) and σ2A/σ2D (<1) revealed the preponderance of non-additive variance for the inheritance of traits studied except for days to 50% curd initiation and harvest index. The results of the experiment suggest the possibility of improvement of these traits through recurrent selection and hybridisation.